Who dictates corporate governance practices in Turkey? The role of ownership structure for XKURY companies. (26th May 2020) - Saygili, Ebru; Saygili, Arıkan Tarık; Taran, Alina
ABSTRACT: This paper investigates the influence of ownership structure on corporate governance practices of Turkish companies listed in Borsa Istanbul Corporate Governance Index (XKURY). It proposes a context-specific ownership structure (founding families, state ownership, foreign ownership from both developed and emerging markets, and institutional investors), and publicly available corporate governance scores as indicators for corporate governance practices. The results of fixed effects panel regression analyses show that state ownership has a negative influence on weighted and non-weighted average corporate governance scores, as mainly determined by shareholder protection and board of directors-related practices during 2010–2017. The evidence regarding the other ownership categories is not sufficient over alternative estimations. Overall, the study provides a critical assessment of the role of ownership in shaping the corporate governance practices of XKURY companies.